2017
DOI: 10.1037/xlm0000300
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of task demands suggests that semantic processing interferes with the formation of episodic associations.

Abstract: Although episodic and semantic memory share overlapping neural mechanisms, it remains unclear how our pre-existing semantic associations modulate the formation of new, episodic associations. When freely recalling recently studied words, people rely on both episodic and semantic associations, shown through temporal and semantic clustering of responses. We asked whether orienting participants toward semantic associations interferes with or facilitates the formation of episodic associations. We compared electroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 76 publications
7
64
0
Order By: Relevance
“…We predicted that the pattern of activity in hippocampus would be consistent with contextually mediated retrieval, with increased activity for correct recalls only, given the role of hippocampus in contextual encoding [3], source memory [12, 13] and recollection [14, 15]. In comparison, we predicted that our other ROIs would differentiate intrusions and deliberations.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We predicted that the pattern of activity in hippocampus would be consistent with contextually mediated retrieval, with increased activity for correct recalls only, given the role of hippocampus in contextual encoding [3], source memory [12, 13] and recollection [14, 15]. In comparison, we predicted that our other ROIs would differentiate intrusions and deliberations.…”
Section: Resultsmentioning
confidence: 96%
“…Based on prior work showing that hippocampal activity correlates with contextual encoding [3], we hypothesized that the hippocampus may also play a unique role in the retrieval of temporal contextual information. It was an open question whether other brain regions within the core memory network would similarly support contextually mediated retrieval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This core prediction of the TAP account has received support from imaging studies (Bauch and Otten, 2012; Fellner et al, 2013; Staudigl and Hanslmayr, 2013; Staudigl et al, 2015; Vogelsang et al, 2016, 2018; Long and Kahana, 2017). Here, we replicate and extend the results from these previous studies by showing that the cortical reinstatement of the encoding brain patterns is only associated with beneficial effects for remembering if the replayed patterns are task relevant.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, previous studies have shown that encoding-related brain activity (i.e., predictive of subsequent memory) is shaped both by the type of processing occurring at encoding and by the overlap between encoding and retrieval processes (Bauch and Otten, 2012; Fellner et al, 2013; Staudigl and Hanslmayr, 2013; Vogelsang et al, 2016; 2018; Long and Kahana, 2017). The typical procedure in these previous studies has been to investigate encoding-related brain activity when explicitly instructing participants to attend to particular attributes during the encoding and retrieval.…”
Section: Introductionmentioning
confidence: 99%